Methionine-aromatic interactions in ABCG2 influence mitoxantrone efflux - Azmir, Nur Amirah Hannan (2020)
The ATP-Binding Cassette (ABC) transporters are one of many families of membrane transport proteins that utilise the hydrolysis of ATP to provide the energy required to actively transport substrates against a concentration gradient. Some ABC transporters have been implicated in cancer multidrug resistance (MDR), where some solid tumours and blood cancers develop reduced chemosensitivity to the antineoplastic agents used to treat them due to these MDR-type ABC transporters having a very diverse substrate specificity incorporating different chemistries. One of these ABC transporters implicated in human cancer MDR is ABCG2. The mechanism behind the ability for ABCG2 to recognise a wide variety of structurally dissimilar substrates is a key question that has yet to be fully answered, with many studies trying to identify both the location of drug binding sites and the translocation pathway for allocrite recognition and efflux.